Question
upstudy study bank question image url

Find the sum function \( (f+g)(x) \) if \( f(x)=\left\{\begin{array}{ll}2 x+5 & \text { if } x<1 \\ x^{2}+3 x & \text { if } x \geq 1\end{array}\right. \) and \( g(x)=\left\{\begin{array}{rr}-4 x+1 & \text { if } x \leq 0 \\ x-6 & \text { if } x>0\end{array}\right. \) Select the correct choice below and fill in the answer boxes to complete your choice. A. \( (f+g)(x)=\left\{\begin{array}{ll}\square & \text { if } x \leq \square \\ \square & \text { if } x>\square\end{array}\right. \) (Simplify your answers. Do not factor.) B. \( (f+g)(x)=\left\{\begin{array}{ll}\square & \text { if } x \leq \square \\ \square & \text { if } \square
Ask by Schmidt Hobbs. in the United States
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( (f+g)(x) = \left\{ \begin{array}{ll} -2x + 6 & \text{if } x \leq 0 \\ 3x - 1 & \text{if } 0 < x < 1 \\ x^2 + 4x - 6 & \text{if } x \geq 1 \end{array} \right. \)

Solution

We begin with the definitions:   f(x) = { 2x + 5 if x < 1,        x² + 3x if x ≥ 1 }   g(x) = { –4x + 1 if x ≤ 0,        x – 6 if x > 0 } Notice that the pieces change at x = 0 (for g) and x = 1 (for f). Therefore, we must break the real line into three regions: 1. When x ≤ 0 (here, f uses its x < 1 definition and g uses its x ≤ 0 definition). 2. When 0 < x < 1 (f still uses its x < 1 definition, but now g uses its x > 0 definition). 3. When x ≥ 1 (now f changes to its x ≥ 1 part and g continues to use its x > 0 piece since 1 > 0). Now, compute the sum (f + g)(x) in each region. Region 1: For x ≤ 0,   f(x) = 2x + 5      (given that x < 1)   g(x) = –4x + 1 So,   (f + g)(x) = (2x + 5) + (–4x + 1) = –2x + 6 Region 2: For 0 < x < 1,   f(x) = 2x + 5       (again, we use the piece for x < 1)   g(x) = x – 6 Thus,   (f + g)(x) = (2x + 5) + (x – 6) = 3x – 1 Region 3: For x ≥ 1,   f(x) = x² + 3x       (use the definition for x ≥ 1)   g(x) = x – 6        (since x > 0) So,   (f + g)(x) = (x² + 3x) + (x – 6) = x² + 4x – 6 Thus the sum function is given by:   (f + g)(x) = { –2x + 6  if x ≤ 0,            3x – 1  if 0 < x < 1,            x² + 4x – 6 if x ≥ 1 } This corresponds to answer choice B with the answer boxes filled as follows: B. (f + g)(x) = { –2x + 6 if x ≤ 0,       3x – 1 if 0 < x < 1,       x² + 4x – 6 if x ≥ 1 }

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To find the sum function \( (f+g)(x) \), we need to consider the different cases for \( f(x) \) and \( g(x) \) based on their defined piecewise functions. 1. **Case 1:** For \( x < 0 \) - \( f(x) = 2x + 5 \) - \( g(x) = -4x + 1 \) - Thus, \( (f+g)(x) = (2x + 5) + (-4x + 1) = -2x + 6 \) 2. **Case 2:** For \( 0 \leq x < 1 \) - \( f(x) = 2x + 5 \) - \( g(x) = x - 6 \) - Thus, \( (f+g)(x) = (2x + 5) + (x - 6) = 3x - 1 \) 3. **Case 3:** For \( x \geq 1 \) - \( f(x) = x^2 + 3x \) - \( g(x) = x - 6 \) - Thus, \( (f+g)(x) = (x^2 + 3x) + (x - 6) = x^2 + 4x - 6 \) Now, combining these results leads us to: A. \( (f+g)(x)=\left\{\begin{array}{ll}-2x + 6 & \text { if } x < 0 \\ 3x - 1 & \text { if } 0 \leq x < 1 \\ x^2 + 4x - 6 & \text { if } x \geq 1\end{array}\right. \) Thus, the correct choice is not option A or B. However, let's format option A with correct values: A. \( (f+g)(x)=\left\{\begin{array}{ll}-2x + 6 & \text { if } x < 0 \\ 3x - 1 & \text { if } x \geq 0\end{array}\right. \) (Simplified)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy